2018
DOI: 10.1016/j.omtn.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

miR-182-5p and miR-183-5p Act as GDNF Mimics in Dopaminergic Midbrain Neurons

Abstract: Parkinson’s disease (PD) is the second-most-frequent neurodegenerative disorder worldwide. One major hallmark of PD is the degeneration of dopaminergic (DA) neurons in the substantia nigra. Glial cell line-derived neurotrophic factor (GDNF) potently increases DA neuron survival in models of PD; however, the underlying mechanisms are incompletely understood. MicroRNAs (miRNAs) are small, non-coding RNAs that are important for post-transcriptional regulation of gene expression. Using small RNA sequencing, we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 52 publications
4
28
0
Order By: Relevance
“…While Pitx3 upregulates miR-133b precursor expression by binding to the promoter region of miR-133b, the 3'-untranslated region (3'-UTR) of Pitx3 is targeted by miR-133b activity. 55 Overall, these reports suggest that there are ongoing interactions between Pitx3, Nurr1, and GDNF, on one hand, and miRNA molecules, on the other hand, that shape the DAergic fate of target cells under differentiation. 39 One such suppressing miRNA molecule, miR-383, inhibits GDNF protein translation and its suppression enhances GDNF expression leading to improved therapeutic potential of mesenchymal stem cells.…”
Section: Underlying Molecular Mechanismsmentioning
confidence: 96%
“…While Pitx3 upregulates miR-133b precursor expression by binding to the promoter region of miR-133b, the 3'-untranslated region (3'-UTR) of Pitx3 is targeted by miR-133b activity. 55 Overall, these reports suggest that there are ongoing interactions between Pitx3, Nurr1, and GDNF, on one hand, and miRNA molecules, on the other hand, that shape the DAergic fate of target cells under differentiation. 39 One such suppressing miRNA molecule, miR-383, inhibits GDNF protein translation and its suppression enhances GDNF expression leading to improved therapeutic potential of mesenchymal stem cells.…”
Section: Underlying Molecular Mechanismsmentioning
confidence: 96%
“…Interestingly, various microRNAs possess a therapeutic potential and provide neuroprotection against neuroinflammation by targeting PD-associated genes ( Table 1 ). In 2018, Roser et al, reported the neuroprotective role of miR-182-5p and miR-183-5p, which downregulated GDNF (glial cell-derived neurotrophic factor) and protected DA neurons against neuronal damage in the PD model [ 49 ]. A cytoplasmic protein NLRP3 belongs to an inflammatory signaling complex, inflammasome, plays a significant role in inflammation-mediated pyrophosphorylation neurodegeneration of DA in substantia nigra par compacta (SNpc) in PD [ 55 , 56 , 57 ].…”
Section: Epigenetics and Neuroinflammation In Pdmentioning
confidence: 99%
“…Levels of miR-148a-3p were associated with glycemic status and glucose levels [ 111 ]. miR-182-5p mediates nigrostriatal protection in the MPTP model of PD [ 137 ]. miR-182-5p was very highly expressed in individuals with prediabetes or type 2 DM, and miR-182-5p was observed to be significantly under-expressed in type 2 DM relative to prediabetes [ 140 ].…”
Section: Microrna Biomarkersmentioning
confidence: 99%